Expansion of the Roman Catholic Church in Ukraine and counteraction of the soviet special services (1920s — 1940s) - Dmytro Vedeneev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Using little-known documents of Soviet special services, the article studies the mechanism and process of proselytism, political and information-related expansion of the Roman Catholic Church onto the non-canonic for the Vatican regions of Central and Eastern Ukraine from the 1920s to 1945. Using the information and analytics of Soviet special services of state security, the article describes structures and educational institutions of the Vatican that promoted the Papal infl uence on the East, collected spy information, turned people into Catholicism and created corresponfi ng atmosphere in society. Particular attention is paid to the activity of the Roman Catholic Church in the Ukraine during World War II, when the Vatican, in fact, took a position of friendly neutrality to Hitler and attempted to use the occupation of the Ukraine for creating long-term positions there. Using the documents of the People’s Commissariat for Internal Aff airs and People’s Commissariat for State Security of the Ukrainian Soviet Socialist Republic and of the USSR, the article studies the activity of state security organs against the Vatican in the Ukraine, including the struggle against the Polish nationalist underground (operation “Sejm”). The article also describes the position of the Kremlin as to the Greek Catholics in the USSR and Greek Catholics of the Ukraine. The conclusion of the article is that the attempts of Rome to intervene in the process of post-war regulations from pro-German positions, the external political ambitions and aggressive Papal policy in furthering its infl uence over the non-canonic territory in the East, serious involvement of the clergy of the Roman Catholic Church and anti-Soviet military underground rebel movement resulted in a direct opposition between the Soviet state security organs and Catholicism in the Ukraine.